Synthesis Of Graphene From Alternative Precursors And The Use Of Quartz Plate For Carbon Source Manipulation - Kairi, Muhammad Izhar (2019)
Graphene is a single layer of carbon atoms arranged in an sp2 -hybridized structure with properties far superior compared to other materials. Research and development in graphene synthesis have been rapidly growing the past few years especially using chemical vapor deposition (CVD). However, in order to move graphene from laboratory scale to commercial domain; graphene synthesis cost need to be continually reduced. In this thesis, this problem was approached from a few angles. One of the study in this thesis demonstrate that rice straw and synthetic biogas, typical wastes from the rice and palm oil production industries can be used as inexpensive carbon source for the production of graphene. In the case of rice straw, the lignocellulosic biomass was first put through thermal pyrolysis in order to obtain the bio-oil and bio-char. Only 0.50 mL of bio-oil was then used as carbon source to sufficiently synthesized 1 cm x 1 cm of large area graphene with good quality (ID/IG = ~0.55) via a two-heating source setup ambient pressure CVD (APCVD) . By doing this, the amount of carbon source going out as effluent is reduced as it has been recovered as side-products prior to graphene growth. The bio-char was also used as carbon source for graphene growth but with a novel and facile carbon trapping assisted APCVD involving customized quartz plate. Here, 2.5 mg of bio-char was encapsulated with quartz plate and Cu foil in a specific arrangement which acted as carbon shields and trapped the carbon active species at high temperature within the confined space of the setup. By implementing carbon trapping, lesser amount of carbon source was needed for graphene growth of the same size; graphene growth efficiency increased around 400 %. Lastly, the effluent of the graphene growth process was converted into syngas when synthetic biogas was used as the carbon precursor with Ni as the catalyst at 900'C in a one-step process; turning waste into wealth.